Levels of domain-specific physical activity at work, in the household, for travel and for leisure among 327 789 adults from 104 countries - Strain, Tessa; Wijndaele, Katrien; Garcia, Leandro; Cowan, Melanie; Guthold, Regina; Brage, Soren; Bull, Fiona C (British journal of sports medicine, 2020)
ObjectiveTo compare the country-level absolute and relative contributions of physical activity at work and in the household, for travel, and during leisure-time to total moderate-to-vigorous physical activity (MVPA).MethodsWe used data collected between 2002 and 2019 from 327 789 participants across 104 countries and territories (n=24 low, n=34 lower-middle, n=30 upper-middle, n=16 high-income) from all six World Health Organization (WHO) regions. We calculated mean min/week of work/household, travel and leisure MVPA and compared their relative contributions to total MVPA using Global Physical Activity Questionnaire data. We compared patterns by country, sex and age group (25–44 and 45–64 years).ResultsMean MVPA in work/household, travel and leisure domains across the 104 countries was 950 (IQR 618–1198), 327 (190–405) and 104 (51–131) min/week, respectively. Corresponding relative contributions to total MVPA were 52% (IQR 44%–63%), 36% (25%–45%) and 12% (4%–15%), respectively. Work/household was the highest contributor in 80 countries; travel in 23; leisure in just one. In both absolute and relative terms, low-income countries tended to show higher work/household (1233 min/week, 57%) and lower leisure MVPA levels (72 min/week, 4%). Travel MVPA duration was higher in low-income countries but there was no obvious pattern in the relative contributions. Women tended to have relatively less work/household and more travel MVPA; age groups were generally similar.ConclusionIn the largest domain-specific physical activity study to date, we found considerable country-level variation in how MVPA is accumulated. Such information is essential to inform national and global policy and future investments to provide opportunities to be active, accounting for country context.